ANALYSIS OF POTENTIAL LAND FOR RELOCATION RESIDENTIAL AREA IN SIMALUNGUN REGENCY - Suhenpi Laia; Ihsan Azhari; Cut Nuraini (PT. Radja Intercontinental Publishing, 2024)
Spatial planning is a structured planning from various considerations of analysis and projection results so as to produce concrete planning to be used as a reference in effective, efficient and sustainable spatial utilization. Emergency or urgent conditions such as disasters, conflicts, strategic projection development and so on that require an existing residential area to be relocated, then the handling has the potential to be inconsistent with spatial planning. Placement of relocation areas is often directed at land with the status